Fashioning Africa : power and the politics of dress - Allman, Jean Marie (African expressive cultures., 2004)
Everywhere in the world there is a close connection between the clothes we wear and our political expression. To date, few scholars have explored what clothing means in 20th-century Africa and the diaspora. In Fashioning Africa, an international group of anthropologists, historians, and art historians bring rich and diverse perspectives to this fascinating topic. From clothing as an expression of freedom in early colonial Zanzibar to Somali women's headcovering in inner-city Minneapolis, these essays expl.